Information Security Protection System for Networked OT Environments of Industrial Control in Smart Manufacturing - Pin-Kuan Chiang; Shang-Liang Chen; Je-Chiao Ku (International Journal of Engineering and Technology Innovation, 2025)
This study develops an innovative information security protection system for end devices in smart manufacturing industrial control environments. By employing six key functionalities—lightweight identity authentication, traffic analysis, key management, personnel authorization control, system status monitoring, and an alarm mechanism—the system addresses the limitations of traditional firewalls. Experimental procedures involved testing the system against common threats, including phishing (fraud), physical intrusion, and Denial of Service attacks. Results demonstrate over 90% success in mitigating these attacks while maintaining operational efficiency. Furthermore, real-time monitoring and alert features enhance data protection and ensure reliable factory operations.